4(x+5)+x=7+2x+x+3

Simple and best practice solution for 4(x+5)+x=7+2x+x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+5)+x=7+2x+x+3 equation:



4(x+5)+x=7+2x+x+3
We move all terms to the left:
4(x+5)+x-(7+2x+x+3)=0
We add all the numbers together, and all the variables
4(x+5)+x-(3x+10)=0
We add all the numbers together, and all the variables
x+4(x+5)-(3x+10)=0
We multiply parentheses
x+4x-(3x+10)+20=0
We get rid of parentheses
x+4x-3x-10+20=0
We add all the numbers together, and all the variables
2x+10=0
We move all terms containing x to the left, all other terms to the right
2x=-10
x=-10/2
x=-5

See similar equations:

| -6x+7(3x-6)=177 | | 4x+44=11 | | 8y–3=69 | | 2+14x=20x+1.5 | | 2/3h=-16 | | 40=5(z-3) | | 3/2w-5/3=-3/2 | | 7m-11=4+2m | | x+67=92 | | 6x-5(6x+39)=153 | | 7(x)=x+6 | | 8x+8x=-1 | | (3x2-5x+1)=(x2+4x+2) | | 25c2-12=1 | | 24-5-10a=-3(4-7a | | 9y–5=22 | | 8x+8x1=-1 | | x-(52-x)=20 | | 15c=90;c=6 | | -1(-2x+1)=9-14x | | 6x-65=3x+13 | | 3(4n+2)=-2(4n+6) | | -9x+30=-5(x+2) | | (8x+9)=(11x+12) | | 2(6x-3)=7(7x-1.2) | | 115+(x+27)=180 | | (4v-3)(v-5=) | | –8s+7=–7s | | 26=6k | | 7(x+5)=24 | | |5m+9|=-31 | | -4r+8+5=-15-3r |

Equations solver categories